Chemical and thermal characterization of wood biomass from non-native tree species in the steppe zone of Ukraine - S. Sytnyk; I. Rula; K. Holoborodko; I. Ivanko; V. Lovynska (Regulatory Mechanisms in Biosystems, 2025)
The growing demand for sustainable and renewable energy sources highlights the importance of exploring biomass from non-native tree species in Ukraine's steppe zone. This study aims to investigate the chemical composition and the r mal decomposition characteristics of wood from non-native tree species ( Acer negundo , Robinia pseudoacacia , Quercus rúbra , Ailanthus altissima ) to evaluate their potential as biomass for energy production. Key wood parameters such as pH, buffering capacity, extractive content, and structural polymers (cellulose, hemicellulose, lignin) were analyzed, revealing significant interspecies variation linked to their biochemical traits and adaptation levels. Thermogravimetric analysis ide n tified three main stages of thermal decomposition and demonstrated differences in thermal stability and decomposition rates among species. Notably, A. negundo exhibited the highest thermal decomposition rate, while R. pseudoacacia showed superior buffering capacity. Correlations between chemical composition and thermal degradation energy requir e ments suggest that species with higher cellulose and lignin content demand greater activation energy for thermo-oxidative breakdown. These findings indicate that non-native tree species, including invasive ones, represent promising biomass sources for energy generation. Moreover, their utilization could serve as a sustainable strategy for controlling species with invasive characteristics, thereby contributing to biodiversity preservation and ecological balance in the region.